Parameter determination of 0.5 hp induction motor based on load factor test - A case study - Ismail, Daut, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/